Calcite Twin Formation, Measurement and Use as Stress–Strain Indicators: A Review of Progress over the Last Decade - Olivier Lacombe (MDPI AG, 2021)
Mechanical twins are common microstructures in deformed calcite. Calcite twins have been used for a long time as indicators of stress/strain orientations and magnitudes. Developments during the last decade point toward significant improvements of existing techniques as well as new applications of calcite twin analysis in tectonic studies. This review summarises the recent progress in the understanding of twin formation, including nucleation and growth of twins, and discusses the concept of CRSS and its dependence on several factors such as strain, temperature and grain size. Classical and recent calcite twin measurement techniques are also presented and their pros and cons are discussed. The newly proposed inversion techniques allowing for the use of calcite twins as indicators of orientations and/or magnitudes of stress and strain are summarized. Benefits for tectonic studies are illustrated through the presentation of several applications, from the scale of the individual tectonic structure to the continental scale. The classical use of calcite twin morphology (e.g., thickness) as a straightforward geothermometer is critically discussed in the light of recent observations that thick twins do not always reflect deformation temperature above 170–200 °C. This review also presents how the age of twinning events in natural rocks can be constrained while individual twins cannot be dated yet. Finally, the review addresses the recent technical and conceptual progress in calcite twinning paleopiezometry, together with the promising combination of this paleopiezometer with mechanical analysis of fractures or stylolite roughness.